Fraud Awareness And Professional Skepticism In Detecting Fraud: Moderation Of Religiosity In Accounting Students - Happy Fitria A’ yuni; Isnaini Anniswati Rosyida; Webbyani Kartikasasri (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Fraud detection is a critical competence for accounting professionals in preventing financial irregularities. This study examines the influence of fraud awareness and professional skepticism on fraud detection ability, with religiosity as a moderating variable. Data were collected from accounting students in Lamongan who had completed auditing courses and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that fraud awareness and professional skepticism significantly improve fraud detection ability. Religiosity also has a significant effect and moderates the relationships among variables by weakening the effect of fraud awareness while strengthening the effect of professional skepticism on fraud detection ability. These findings highlight the importance of integrating cognitive competence, professional attitudes, and ethical values in accounting education.